2016
DOI: 10.1002/2016gl069121
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of recent climate change on trends in baseflow and stormflow in United States watersheds

Abstract: Characterizing the impacts of climatic change on hydrologic processes is critical for managing freshwater systems. Specifically, there is a need to evaluate how the two major components of streamflow, baseflow and stormflow, have responded to recent trends in climate. We derive baseflow and stormflow for 674 sites throughout the United States from 1980 to 2010 to examine their associations with precipitation, potential evapotranspiration, and maximum/minimum temperature. The northeastern (NE) and southwestern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 61 publications
8
80
1
Order By: Relevance
“…These values compare well with modelled increases in average annual recharge in Grand River basin to the west of the study area in the order of 2.5 mm year −1 for 1960–1999 (Jyrkama & Sykes, ). They are also consistent with partial evidence of increasing trends in WY P and groundwater recharge along the ORM reported here, and Ficklin et al's () observation of good correspondence between temporal trends in BF and P at the national scale in the United States. Any increase in WY P in the ORM region has been partly countered by increasing PET , which is greatest in summer.…”
Section: Discussionsupporting
confidence: 91%
“…These values compare well with modelled increases in average annual recharge in Grand River basin to the west of the study area in the order of 2.5 mm year −1 for 1960–1999 (Jyrkama & Sykes, ). They are also consistent with partial evidence of increasing trends in WY P and groundwater recharge along the ORM reported here, and Ficklin et al's () observation of good correspondence between temporal trends in BF and P at the national scale in the United States. Any increase in WY P in the ORM region has been partly countered by increasing PET , which is greatest in summer.…”
Section: Discussionsupporting
confidence: 91%
“…A finding of no significant trend is a common result among studies that use the Mann-Kendall test to identify trends among several sites [39,40], and is more common among precipitation than discharge [36]. This may be due to a break in classification.…”
Section: Trendsmentioning
confidence: 98%
“…We chose to show trends at alpha values and not outside of those thresholds; as a result, we conclude a significant trend at α = 0.09 but not at 0.11. Some studies report the Z score calculated by the Mann-Kendall test [39,40], which describes the magnitude of the trend and is thus continuous from very strong trend to very little or no trend; but we focused on statistical significance rather than a graduated scale for a less nuanced classification. Additionally, our study uses easily obtained data over large areas-areas with a dry summer climate across the globe-and coverage over these areas is not comprehensive.…”
Section: Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yusoff et al, 2002;Brabets and Walvoord, 2009;Huntington et al, 2009;Xie et al, 2010). Recently, Ficklin et al (2016) also showed that climate driven changes in baseflow in United States watersheds vary across the nation and seasons; except in the northeast where climate change contributed to consistent baseflow increase during fall and winter and decrease during all seasons in the southwest. In the Midwest and Great Plains regions, analysis of historical streamflow records revealed increasing trends in streamflow and baseflow due to the influence of climate (e.g.…”
Section: Introductionmentioning
confidence: 99%